2016
DOI: 10.1016/j.jspd.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Does the Type of Metal Instrumentation Affect the Risk of Surgical Site Infection in Pediatric Scoliosis Surgery?

Abstract: Level II, prognostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…7,18 In previous investigations, such infectious complications have consistently been attributed to increased implant density, fusion to the pelvis, residual postoperative curve magnitude, longer operative times, neurogenic bowel/bladder dysfunction, body mass index > 95th percentile, degree of cognitive impairment, use of allograft bone tissue, and presence of gastrostomy/jejunostomy tubes or ventriculoperitoneal shunts. 1,3,5,8,15,17,18,21 Ultimately, nutritional depletion has been additionally linked to slow wound healing and immunological compromise, contributing to heightened risk for infection. 5 In the present cohort, pulmonary comorbidity (p = 0.001), increase in weight from preoperative to follow-up (p < 0.01), and residual lumbar lordosis at follow-up (p = 0.015) were the most reliable and consistent risk factors for SSI.…”
Section: Discussionmentioning
confidence: 99%
“…7,18 In previous investigations, such infectious complications have consistently been attributed to increased implant density, fusion to the pelvis, residual postoperative curve magnitude, longer operative times, neurogenic bowel/bladder dysfunction, body mass index > 95th percentile, degree of cognitive impairment, use of allograft bone tissue, and presence of gastrostomy/jejunostomy tubes or ventriculoperitoneal shunts. 1,3,5,8,15,17,18,21 Ultimately, nutritional depletion has been additionally linked to slow wound healing and immunological compromise, contributing to heightened risk for infection. 5 In the present cohort, pulmonary comorbidity (p = 0.001), increase in weight from preoperative to follow-up (p < 0.01), and residual lumbar lordosis at follow-up (p = 0.015) were the most reliable and consistent risk factors for SSI.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,23-25 Soultanis et al found that 5 of 50 stainless steel implants compared with 0 of 40 titanium implants developed infections ≥ 1 year after surgery, postulating that a more stable construct led to greater bone adhesion on the implant resulting in a thinner glycocalyx biofilm reducing the risk of infection. 23 However, Wright et al found that the type of metal instrumentation did not affect the risk of SSI, 26 and that surface imperfections and rougher microtopography may be more important factors in harboring bacteria. 27 Our findings support the use of titanium implant as the material had the lowest late infection rate (0.2%) and in that no patient who underwent IE, of which most implants were titanium, developed a subsequent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Literature toward this topic is controversial. While some studies [22][23][24] emphasized a protective role of TiAl rods compared with stainless steel, others 25,26 showed no difference in infection rate between the various materials.…”
Section: Discussionmentioning
confidence: 99%